Phenomenology of a Living Word: a Tribute to the Memory and Dignity of the Unforgettable (Linguostylistic Studies, 2020)
The article elucidates the issues of the general anthropocentric orientation of modern linguistic research, taking into account the “human” factor and through the prism of subjective vision of the world. Scholars believe that a word is not only a way of exchanging thoughts but also a form of interaction of people, a means of stimulating their consciousness, will and emotions, a way to achieve mutual understanding in society, or a failure to achieve it.The article examines the phenomenological aspects of the Belarusian word, using the antinomy memorable and unforgettable  as a case study. The phenomenon of the unforgettable is associated with the archaeological approach to the obvious reality embodied in the word, the study of the deep semantic structures of the language, its “internal” forms. Using the phenomenological approach, the study seeks to reveal the phenomena of multi-vector word usage in live speech and interpret their semantics. In the focus is the language as the prerequisite for the study of the life world – a phenomenological reality embodied in the continuum of the living word.The characteristic features of a living word are justified, and a living word is considered not as a part of a sign system (which is accepted in the traditional approach) but as the reality of metalinguistic creativity. The distinguishing features of a living word are identified: eidetic nature, impressive (graphic) nature, text formation ability, lack of pragmatic significance, non-discursiveness, semantic elusiveness (“diverse semantic vectoriality”).The significance of the results of the work is obvious since they stimulate the continuation of the phenomenological study of Belarusian language reality. The linguistic phenomenology in this context can be considered as a promising direction that can explain the principle of linguistic variability of a living word, as well as the contradiction between symbols and their infinity of meanings expressed by them.
Keywords: unforgettable,; memory,; phenomenology,; archeology of thinking,; a living word.